Upaya Meningkatkan Kemampuan Berbicara Melalui Metode Bermain Peran Pada Anak Usia 4-5 Tahun di TK IT Nurul Fikri Padangsidimpuan - Elva Wardani Harahap; Hasanah Hasanah; Hesi Kartikasari Harahap (Jurnal Pendidikan Tuntas, 2023)
With language, everyone will have the ability to express their thinking activities and feelings which can be understood and interpreted together by other people. The aim of this research is to improve speaking skills through role playing methods in children aged 4-5 years at TKIT Nurul Fikri Padangsidimpuan. The type of research is Classroom Action Research which is a strategic way for educators to improve and improve educational services in the context of classroom learning. The results of the research were that in cycle 1, 58% of children were still not developing, while 20% of children were starting to develop. Furthermore, in the category developing as expected, only 16%, followed by 6% in the category developing very well. The improvement figures obtained have not reached the standard of success, therefore the teacher tries again in the second cycle. The results of the research in the second cycle were that 42% of children had reached the developing category as expected. Furthermore, 34% of children had begun to develop their speaking abilities. And there are 14% of children who have developed very well in their speaking skills when learning through the role-playing method. However, there are still 10% of children remaining in the underdeveloped category. The increase in the average speaking ability of children aged 4-5 years at TKIT Nurul Fikri Padangsidimpuan in the second cycle has reached indicators of success, so that the classroom action research at TKIT Nurul Fitri Padangsidimpuan has been considered successful. Furthermore, consistency and a supportive environment is needed, where children feel safe and open to express their thoughts and feelings in the form of speaking skills. Keywords : Speaking Ability, Role Playing, Children